Indicative for Corporate Real Estate (CRE) performance in Malaysian public listed companies - Sulaiman, Nurul Nabila (2013)
Corporate real estate management (CREM) is about the management system for non-real estate company. While, corporate real estate (CRE) is about an asset owned by non-real estate company. Since CREM is still new in Malaysia, many corporate members does not know the right way to manage their CRE and how to generate profit from it. They do not see the potential of CRE performance if it is fully utilised. So, the purpose of this research is to find out a tools that can measure CRE performance in a firm. The existence of CRE performance measurement tools will help to prove and convince the corporate members about CRE potential in generating other income for company. At the end of this research, it may guide the corporate members in planning their CRE strategically to generate more income for firm.